Inequality, fairness and social capital - Fehr, Dietmar; Rau, Hannes; Trautmann, Stefan T.; Xu, Yilong (European economic review, 2020)
Inequality is often associated with negative societal consequences, but identifying a causal relationship is a daunting task. We provide evidence on the impact of unjust economic inequality on social interactions. Using a large-scale controlled experiment, we document that unjust inequality results in a significant decline in trust and trustworthiness. This erosion of social capital is associated with pessimistic beliefs about others’ behavior and is muted if there is no direct link between the income-generating process and social interaction. Finally, our data do not support the view that higher status or wealth affects pro-social attitudes: the successful are always more generous, whereas unsuccessful persons display the least efficient and generous behavior regardless of the status of the person who they interact with.
Gesehen am 16.11.2020